THE PREVALENCE OF TRADITIONAL CARDIOVASCULAR RISK FACTORS IN PATIENTS WITH RHEUMATOID ARTHRITIS AND IN THOSE WITH PSORIATIC ARTHRITIS - Yo. U. Saidov; I. Yo. Odilzoda; S. M. Khasanzoda; O. D. Okhonova; Kh. R. Mahmudov (Научно-практическая ревматология, 2020)
Objective: to comparatively analyze and estimate the prevalence of traditional cardiovascular risk factors (RFs) and the blood lipid spectrum in patients with rheumatoid arthritis (RA) and in those with psoriatic arthritis (PsA).Subjects and methods. The investigation enrolled 48 patients (41 females and 7 males) (mean age, 51.3±4.3 years) with RA who fulfilled the 1987 American College of Rheumatology (ACR) criteria and 46 patients (25 females and 21 males) (mean age, 49.6±3.8 years) with PsA fulfilling the 2006 Classification Criteria for Psoriatic Arthritis (CASPAR) criteria who were treated in Dushanbe City Medical Center (CMC) Two in 2012 to 2019. The traditional and disease-related RFs of cardiovascular events (CVEs) were analyzed to identify the total cardiovascular risk using the SCORE and 2010 SCORE/EULAR scales; duplex scanning of the carotid arteries was performed to measure intima-media thickness and to identify atherosclerotic plaques; the blood lipid spectrum (total cholesterol (TC), triglycerides, low-density lipoprotein cholesterol (LDLC) and high-density lipoprotein cholesterol (HDLC)). The atherogenic index (TC-HDLC/HDLC) was calculated to determine the ratio of atherogenic to antiatherogenic lipoproteins.Results and discussion. The most common RFs for CVEs in the examined patients with RA and in those with PsA were hypertension (64.5 and 58.6%, respectively) and dyslipidemia (58.2 and 69.2%). It was found that systemic inflammation and pharmacotherapy for RA and PsA were actively involved in the formation of an atherogenic lipid profile and that the incidence of CVEs increased in patients with RA and in those with PsA who had two or more traditional and the so-called disease-related RFs.Conclusion. Our findings suggest that the development and progression of a wide range of CVEs in patients with RA and in those with PsA are based on the cumulative effect and complex interaction of chronic systemic autoimmune inflammation, traditional cardiovascular RFs, and long-term and uncontrolled use of nonsteroidal anti-inflammatory drugs and glucocorticoids, which assumes that CVEs have a multifactorial nature in RA and PsA.